An Overview: Effect of Treated Waste Water on Properties of Concrete: Assessing the Impact of Treated Waste Water on Concrete Strength and Properties (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Water is a critical environmental issue and water supplies and water quality are becoming more limited worldwide. The study deals with the effect of different type of treated waste water on properties of strength of concrete such as compressive strength, tensile strength, flexural strength and workability with respect to potable water. Water sample were used as treated waste water which was analysed for its chemical properties in laboratory. In that use of concrete mix of M30 the potable waste water was replaced with treated waste water.